What is the Diagnosis? - Costa, Eduardo Rodrigues Bento; Pegoraro, Vagner Rossato; Vellenich, Andreza Chaguri (JOURNAL OF CARDIAC ARRHYTHMIAS, 2020)
Patient from male gender, 78 years of age, referred to 24 h Holter exam due to complaints of being tired and palpitation. The hypothesis diagnosis or medical history was not described. The exam was recorded in a private clinic and digitally forwarded to analysis in our service. After the search for clinical information, we heard that the patient is a cardiac pacemaker user; however, there was neither information regarding reason or date of implant, brand, or model of the pulse generator nor programming of the device.